Math, asked by vishu9116, 11 months ago

Solve m² +6m-27=0
it simple can anyone make this ​

Answers

Answered by VIVEKPARIDA
2

Answer:

The first term is,  m2  its coefficient is  1 .

The middle term is,  -6m  its coefficient is  -6 .

The last term, "the constant", is  -27 

Step-1 : Multiply the coefficient of the first term by the constant   1 • -27 = -27 

Step-2 : Find two factors of  -27  whose sum equals the coefficient of the middle term, which is   -6 .

     -27   +   1   =   -26     -9   +   3   =   -6   That's it

Step-3 : Rewrite the polynomial splitting the middle term using the two factors found in step 2 above,  -9  and  3 

                     m2 - 9m + 3m - 27

Step-4 : Add up the first 2 terms, pulling out like factors :

                    m • (m-9)

              Add up the last 2 terms, pulling out common factors :

                    3 • (m-9)

Step-5 : Add up the four terms of step 4 :

                    (m+3)  •  (m-9)

             Which is the desired factorization

Answered by nitashachadha84
11

m² +6m-27=0

on transposing the terms

m² + 6m = 27

 {m}^{2}  + m = \huge  \frac{27}{6}  =  \frac{9}{2}

m + m = \huge  \sqrt{ \frac{9}{2} }

2m =  \huge \sqrt{ \frac{9}{2} }

 \implies \: m =   \huge\sqrt{ \frac{9}{2 \times 2} }  =  \sqrt{ \frac{9}{4} }

 \boxed{m = \huge  \frac{3}{2} }

<b><marquee>Mark me as brainliest

Similar questions